Evaluation Earned Value Management for Teaching Time and Cost Performance in Civil Engineering Education - al Qordhowi, Andrian Firdaus Yusuf (Global Education Journal, 2025)
The alignment between civil engineering education and industry demands requires learning models that effectively integrate theoretical knowledge with real project-based analytical skills. In construction management courses, students are expected to master not only conceptual frameworks but also practical tools for evaluating project performance. This study aims to examine the effectiveness of integrating construction management techniques particularly Earned Value Management (EVM) into civil engineering education by using river embankment development projects as authentic learning case studies. The research adopts a quantitative evaluative approach with an explanatory design, involving undergraduate civil engineering students enrolled in construction management courses. Learning outcomes were assessed through students’ ability to analyze time and cost performance using key EVM indicators, including Schedule Performance Index (SPI), Cost Performance Index (CPI), and Estimate at Completion (EAC). The results indicate that the use of real infrastructure project cases significantly enhanced students’ analytical competence in identifying schedule delays, cost inefficiencies, and their interdependencies. However, the findings also reveal limitations in students’ capacity to propose adaptive corrective strategies, reflecting gaps between analytical understanding and decision-making skills. The study concludes that integrating construction management techniques through project-based learning strengthens cognitive and applied learning outcomes but requires complementary pedagogical strategies to foster higher-order problem-solving abilities.